Museum Seni Patung Sebagai Ikon yang Memperkuat Citra Kawasan - Ai Nurjanah, - (2020)
Museum, with its main function as a conservation media, may transform its building as an icon of an area. Sculpture, as a part of visual arts, has become an expression of the people's culture with its beauty and evocative elements. The substantial role of museum and its existence within the society have become a strategy to strengthen the image of its surrounding area. To discover the meaning of a city, the understanding on layout, activities and history are necessary. These must be taken into account to preserve and develop museum as a cultural experience and to strengthen the area's image. Timeline-based exhibition flow is made to enhance emotional impression and supported with the use of materials, space scale and outdoor space that can be accessed by anyone. The atmosphere is developed following the North - South imaginary line of Bandung City in the direction of Gedung Sate - Mount Tangkuban Parahu. Keywords: museum, form, activity, image.